Diagnosis and treatment of biliary atresia in children (Pain medicine, 2022)
Abstract. There are relatively few severe liver diseases in childhood. Biliary atresia is one of the most difficult. Early diagnosis of this disease is the basis of the subsequent treatment algorithm. In this article, we want to present the main criteria for diagnosing biliary tract pathology in newborns and young children, as well as draw the attention of pediatricians and neonatologists to the difficulties that arise in their diagnosis. Despite the rarity of these diseases, biliary atresia, as well as other rare liver diseases, should always be considered in the diagnosis of longterm hyperbilirubinemia. Due to early diagnosis and subsequent Kasai operation, the possibility of liver transplantation, in the last two decades, there has been significant progress in the treatment of children with biliary atresia.
Keywords: hyperbilirubinemia; cholestatic jaundice; biliary atresia; hepatoportoenterostomy by Kasai; liver transplantation